Educational Planning in Nigeria: Problems, Prospects and Possible Solutions - ThankGod PETER,; Murtala SHEHU; Innocent HARUNA; Mathew Adetimehin ADELEGAN (Researchparks Publishing, 2023)
Educational planning is vital to the realization education objectives. Educational planning is crucial in the implementation of educational programme and projects. Educational planning in Nigeria is plagued with many challenges. This paper examined the problems and prospects of educational planning in Nigeria and suggested possible solutions to address the problems facing educational planning in Nigeria.